Prison, Human Rights, and Imprisonment - Sánchez Vega, Alexis (2019)
This article aims to analyze the last five years of the Costa Rican Penitentiary System, to show in which state it is and what the public policy proposals have been to address the problem of incarceration of persons and the problems derived from this activity.  A theoretical and methodological review is carried out to account for prison overpopulation and the prison as a reforming institution. The discussion is considered important when visualizing the role of the prison system, which has been instrumentalized as a social mechanism and given a justification that allows it to be considered as a solution to the country's delinquency problem. Prison has been given the role of the resocializing entity and the "right" place for people considered as criminals to serve their prison penalties. However, the advent of penal and citizen security reforms from the early twenty-first century led to an increase in the population deprived of liberty and the emergence of two phenomena: overpopulation and overcrowding. This has caused both elements to violate the rights of people imprisoned. Therefore, a proposal is presented to reduce the effects of the use of prison and thereby improve the quality of life of people in incarcerated, based on a different institutional and criminal policy.